TOWARDS QUALITY ISLAMIC EDUCATION: Madrasa Teachers’ Views on School Climate in East Java - Mustofa, Ali (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2021)
Abstract: This research explores teachers’ views on school climate, related to teacher’s age, gender, and teaching experience for Madrasah Tsnawiyah teachers. Research is carried out to realize the quality of Islamic education. The 370 teachers were given a school climate perception scale adapted from the Comprehensive School Climate Inventory (NSCC) developed by Cohen through Google Form. The scale includes four aspects: safety, teaching and learning, relationships, and the environment, with a Cronbach’s Alpha reliability value of 0.700. From the data collection results, it was found that the age and length of the teacher’s teaching were significantly related to the teacher’s view of the school climate. Teachers who have long teaching experience have a more positive perception than teachers who have little teaching experience. Likewise, the teacher’s age shows that older teachers give a better view of the school climate than younger teachers. On the other hand, gender is not significantly related, meaning that male and female teachers have the same view of the school climate.Keywords: school climate, age, gender, teaching experience